Three new species of the family Idyanthidae (Copepoda, Harpacticoida) from sublittoral zones around the Korean Peninsula - Jong Guk Kim; Kyuhee Cho; Jimin Lee (PeerJ)
There are few taxonomic studies of the harpacticoid family Idyanthidae Lang, 1944 in the Pacific Ocean. As a first report of the family in this region, one species of the monotypic genus Idyellopsis Lang, 1948 and two species of the genus Idyella Sars, 1905 are described from sublittoral habitats around the Korean Peninsula. Idyellopsis orientalis sp. nov. is distinguished from the type and only species of the genus, Idyellopsis typica Lang, 1948, in the length:width ratio of the body and genital double-somite, length of caudal seta I, and structure of the female P5 baseoendopod. Idyella dolichi sp. nov. and Idyella exochos sp. nov. share the armature of the female P5 exopod with four setae with Idyella exigua Sars, 1905, Idyella major Sars, 1920, and Idyella pallidula Sars, 1905. However, the two new species differ from the three European species in the armature of the terminal segment of the P1 endopod and female P5 baseoendopod, and in the shape of the genital double-somite. The male of Idyella dolichi sp. nov. also has two distinct features: the distal two segments of the P2 endopod are completely fused, and the third segment of the antennule has a prominent outer projection. The geographical distribution of Idyellopsis and Idyella is extended by the discovery of three new species in Korean waters. We also discuss a possible phylogenetic relationship among members of family Idyanthidae at genus level.